Understanding Alzheimer's Disease - Cutler, Neal R. (Book collections on Project MUSE., 1996)
"This book describing the most current knowledge of how and why Alzheimer's arises is written for those who have the disease, for their families and caregivers, for professionals who serve such people, for teachers, and for anyone with a general interest in the disease. An important feature of this book is clear explanation of the basic biology of Alzheimer's. A large section is devoted to the subject of caring for affected individuals, including legal and financial-planning advice and pointers for finding outside support services."--Jacket.